2020
DOI: 10.5433/1679-0359.2020v41n1p95
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of aluminum and cadmium toxicity by biochar and its potential toxicity to sorghum

Abstract: Highlights:Use of biochar to mitigate soils contaminated by trace elements. Pyrolysis as an alternative to sewage sludge disposal in the environment. Some mechanisms involved in the alleviation of soil acidity by biochar. A rapid and simple test to assess biochar toxicity. Biochar as a strong and effective sorbent for aluminum and cadmium. AbstractBiochar has been used as an alternative in organic wastes management and to alleviate trace elements toxicity. The aim of this research was to use a rapid and simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…However, the lower root dry mass yield can be attributed to the immobilization of silver ions (Ag + ) by biochar. In general, due to ash content, rich in alkali metal oxides and hydroxides (De Almeida et al, 2020), biochars raise the medium's pH, and, consequently, precipitation of cationic metal ions can occur (Rajapaksha et al, 2016;Rizwan et al, 2016). Besides, biochars are very efficient adsorbents of cationic metal ions due to the high surface area, particle porosity, and functional groups that exhibit negative electric charges (Bian et al, 2014;Lu et al, 2014;Tang et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…However, the lower root dry mass yield can be attributed to the immobilization of silver ions (Ag + ) by biochar. In general, due to ash content, rich in alkali metal oxides and hydroxides (De Almeida et al, 2020), biochars raise the medium's pH, and, consequently, precipitation of cationic metal ions can occur (Rajapaksha et al, 2016;Rizwan et al, 2016). Besides, biochars are very efficient adsorbents of cationic metal ions due to the high surface area, particle porosity, and functional groups that exhibit negative electric charges (Bian et al, 2014;Lu et al, 2014;Tang et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…As the soil pH increases due to biochar, Al 3+ is converted to Al(OH) 2+ , Al(OH) 2 + , and Al(OH) 3 , reducing the toxicity of aluminum to plants (Qian, Chen, & Hu, 2013;Tang et al, 2013). In addition to increasing soil pH, biochar can strongly adsorb the monomers Al(OH) 2+ and Al(OH) 2 + (Almeida et al, 2020), because of its high aromaticity and specific surface area (Qian et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have shown the potential of biochar to neutralize soil acidity and increase soil phosphorus (P) content (Almeida et al, 2020;Alves et al, 2021). However, there are few studies on the effects of the interaction between biochar, liming, and phosphate fertilization on soil fertility and plant productivity.…”
Section: Introductionmentioning
confidence: 99%